Cubic CuCo2O4 microspheres with FeO nanowires link as free-standing anode for high-performance lithium ion batteries. Issue 2 (1st February 2016) - Cheng, Jianliang; Li, Xinhai; Wang, Zhixing; Guo, Huajun; Peng, Wenjie; Hu, Qiyang
Abstract: Transition metal oxides show great potential in the area of energy storage. However, these materials suffer from structural damage, resulting in poor cycle performance. In this work, a novel structure, CuCo2 O4 microspheres with FeO nanowires link on Ni foam is prepared and directly used as binder- and conductive agent-free anode for LIBs. In this construction, the CuCo2 O4 is the main active material and the FeO nanowires have good mechanical adhesion with Ni substrate and CuCo2 O4 microspheres. With such predominant design, this composite shows good electrochemical performance. It delivers a reversible capacity of 1258 mA h g − 1 and maintains 92.3% capacity retention at 100 mA g − 1 . Even performed at high rate, it also possesses good rate capability, exhibiting 526 mA h g −1 at 4000 mA g − 1 . Furthermore, this smart structure possesses good electrochemical kinetics.